The special judo fitness test in competitor preparation diagnostics during an annual training period - Szmatlan-Gabrys, U.; Garnys, M.; Gabrys, T.; Ozimek, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: A correlation analysis carried out between the values of capacity indicators, and special fitness, is a tool allowing us to determine the relationship and interaction between competitor preparation periods, and the appropriateness of the choice of supervision methods. (Franchini et al 2009 ) The aim of the research was to either confirm, or refute the hypothesis concerning the universal character of the SJFT in the evaluation of the preparation of the judoist. Methods: During the annual training period capacity indicators of 23 international sport level judoists aged 19-26, in 66-81 kg weight categories were registered. The subjects carried out three tests four times: Wingate Test with Pmax registration (W/kg, b.w) WTOT(J/kg, b.w) and IF(%), SJFT, registering index; during the treadmill Incremental Exercise the VO2, VCO2, VE , and HR were registered. (K4B2, Cosmed) The character and strength of the relationship between test indicators during the general preparation period (GPP), the special preparatory periods (SPP), and the competition period, were determined by means of a statistical analysis. Results: The statistically relevant correlations between the aerobic, anaerobic, and special capacity indicators divided the indicators into two indicator groups assigned to training periods. In GPP- SJFT, and VO2max (r=.397, p.05), as well as IF (r=-.396, p.05), SPP- SJFT with WTOT (r=.411 p.05),and Pmax (r=.405 p.05), CP - SJFT with WTOT (r=.425 p.05), and IF (r=-.461 p.05) Discussion: The research did not confirm the universal evaluation of special preparation of the judoist by means of the SJFT (Franchini 2009) A lack of relationship was shown between aerobic capacity and SJFT in SPP, and CP , as well as with anaerobic capacity in GPP. The statistically relevant relationship between the SJFT index and aerobic metabolism which was indicated by the research by Franchini et. al. (2011) was not confirmed. In SPP, and CP, WTOT correlates with SJFT index. Periodically the IF value shows a relationship with SJFT index value. (GPP, and CP r= -.396, r=-.461, respectively). In GPP aerobic, and in SPP, and CP anaerobic training measures dominate. Then, there appears also relationship between IF, WTOT, Pmax, and SJFT index. It can be stated, that SJFT is a tool evaluating the special preparatory judoist during training periods characterized by a great deal of anaerobic training loads. In training periods in which judoist passes from metabolic, anaerobic training loads to metabolic aerobic ones, SJFT is not a good judoist evaluation tool.